The Effect of Service Quality on Lecturers' Workload on Lecturer Satisfaction at Pattimura University Ambon - Anthoneta Matakupan; Marsintya de Rooy; Caroline van Room; Rivaldo Patawala; Valiant C Leihitu (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
In service quality, the measure is not solely determined by the provider, but more so by the recipients. They are the ones who benefit from the service, and therefore can measure service quality against their expectations to meet their satisfaction. Service quality must begin with user needs and end with user satisfaction. This study aims to analyze and explain the influence of service quality variables, including: professionalism and skills, attitudes and behaviors, accessibility and flexibility, reliability and trustworthiness, recovery, reputation and credibility, and lecturer satisfaction. The population of this study was all lecturers at Pattimura University. The sampling technique used was purposive sampling, with a sample size of 117 respondents. The analysis used a Likert scale and multiple linear regression analysis with SPSS version 24 software to process the data. The results showed that all service quality variables significantly influenced lecturer satisfaction, with recovery being the most influential. It is recommended that Pattimura University evaluate the service quality, including ease of access anywhere, as some respondents/lecturers expressed that service quality is still lacking. Future researchers can develop other variables as mediators, and the research object could be banks with a specific number of products offered.